Publicidad programática y protección de datos personales - Revoredo Palacios, Abel (2021)
The author introduces the concept of programmatic advertising, which exploits the extended use of the internet to enhance the content users receive through adverts. He explains some relevant elements to better understand its use, and discusses whether personal data is involved in its practice. Thus, he compares the applicable legislation in the European Union and Peru.